Evaluation of Redox Status in Patients with Hepatitis B Virus in Zahedan, Iran - Hosnie Hoseini; Soudabeh Etemadi (Golestan University Of Medical Sciences, 2020)
Background and objectives:  Redox status can be defined as an increase in oxidant and/or a decrease in antioxidant capacities. There is limited information about the redox status of patients with hepatitis B virus (HBV) infection. Therefore, we aimed to evaluate the redox status of patients with HBV infection in Zahedan, Southeast of Iran. Methods: This study was carried out in 2019 on 25 HBV patients and 25 healthy individuals. The level of malondialdehyde (MDA) was measured as a marker of lipid peroxidation. Superoxide dismutase (SOD) activity was also measured. Data were analyzed using SPSS software (version 17) at significance of 0.05. Results:  The MDA level in patients (5.3 ± 2.511 n/ml) was significantly higher than in controls (3.48 ± 0.516 n/ml) (P <0.01). Moreover, SOD activity was significantly lower in HBV patients (125.05±55.545 n/μl) compared to healthy controls (271 ± 74.236 n/μl) (P<0.01). Conclusion: Our results show that patients with HBV infection have higher serum MDA level and lower SOD activity compared to healthy individuals. This can cause liver damage and aggravate the complications in hepatitis B patients